Synthesis and biological activity of acetylacetone thiosemicarbazone and their metallic complexes - Kumar, Sandeep; Kumar, Nitin (International Current Pharmaceutical Journal, 2013)
In present work, Ligand acetylacetone thiosemicarbazone and their 11 complexes of the type ML2X2, ML2X, where M = Cu(II), Cd(II), Co(II), Zn(II), Hg(II); L = acetylacetone thiosemicarbazone; X = Cl, NO3 or CH3COO; X = SO4 have been synthesized and characterized with the help of molar conductance, magnetic susceptibility measurements, infra-red and ultra-violet spectroscopy. The spectral data revealed that the thiosemicarbazone act as bidentate ligand, making use of thionic sulphur and the azomethine nitrogen atom for co-ordination to the central metal atom. All the compounds have been screened for their antibacterial activity against Gram positive bacteria Staphylococcus aureus, Staphylococcus epidermidis and Gram negative bacteria Escherichia coli and Pseudomonas aeruginosa. Some of complexes exhibited appreciable activity. DOI: http://dx.doi.org/10.3329/icpj.v2i4.14057 International Current Pharmaceutical Journal, March 2013, 2(4): 88-91